(untitled) (Journal of Philosophy Culture and Political Science, 2015)
The article deals with the peculiarities and urgent issues of Islamic movements in the present-day Kazakhstan. The research shows the negative effects and consequences of such Islamic movements, spread throughout the Republic. It describes the origins of these Islamic movements conducting missionary work as well as their work in the Republic of Kazakhstan. The article examines the damage caused by such Islamic movements as Hizb ut-Tahrir and Salafism on the republic’s territory and raises the problem of religious literacy. It gives the current statistics and the information on the measures taken by the authorities concerning this problem. The author examines the reasons for the spread of the unconventional Islamic movements in our society and gives a number of suggestions as to prevent them from growing. The article aims at preventing the spread of extremist and terrorist doctrines and giving thorough information about Islamic movements of the Republic of Kazakhstan.